Modélisation de l'avancée des espèces arbustives dans la région d'Umiujaq, Nunavik - Lemay, Marc-André (Université Laval, 2017)
A circumpolar increase in shrub cover has been underway in northern ecosystems in recent decades, but the landscape-scale drivers of this shrubification are not well understood. In this study, we adopted a land cover change modelling approach to identify variables driving shrub cover increase near Umiujaq, Québec. We modelled land cover change in this area over the period 1990/1994-2010 and used these models to generate spatially explicit predictions of shrub cover increase. We found that shrubs tended to colonize low-elevation areas and moderate slopes more easily, whereas their cover was more likely to increase in the vicinity of existing shrub stands. The predicted probabilities of shrub cover increase in the region were consistent with patterns of change inferred from field observations, but not from recent local changes in NDVI (normalized difference vegetation index). Our findings warrant further research on the large-scale impacts of shrubification on ecosystem function and the link between land cover changes and variations in indices derived from remote sensing. Tableau d'honneur de la Faculté des études supérieures et postdoctorales, 2016-2017 On observe présentement une augmentation du couvert arbustif à l'échelle circumpolaire, mais les déterminants de cette arbustation à l'échelle du paysage sont encore mal compris. Dans cette étude, nous avons adopté une approche de modélisation des changements de couvert afin d'identifier les variables déterminant l'augmentation du couvert arbustif à proximité d'Umiujaq, Québec. Nous avons modélisé les changements survenus entre 1990/1994 et 2010 et avons utilisé ces modèles afin de générer des prédictions sur l'augmentation du couvert arbustif. Nous avons trouvé que les arbustes tendent à coloniser plus facilement les sites à basse altitude ainsi que les pentes modérées, alors que leur couvert est plus susceptible d'augmenter à proximité de peuplements arbustifs déjà existants. Les probabilités d'arbustation prédites dans la région étaient cohérentes avec les ...